Corm damage caused by banana weevils Cosmopolites sordidus (Germar) collected from different banana growing regions in Uganda - Charles K. Twesigye; Kenneth Ssekatawa; Andrew Kiggundu; Wilberforce Tushemereirwe; Enock Matovu; Eldad Karamura (Agriculture & Food Security, 2018)
Abstract Background In this study, both healthy tissue culture plantlets and maiden suckers of the Nakitembe cultivar were used to assess the damage level variation caused by banana weevils collected from different banana growing regions. Seventy-nine (79) tissue culture plantlets and fifty (50) suckers were established in buckets in a randomized complete block design for 5 months. Ten adult weevils (5 females and 5 males) were introduced at the base of each plant, and the buckets were covered with a weevil proof mesh. Weevil damage was estimated as a percentage at 60 days after the weevil introduction by estimating the peripheral damage (PD), total cross section corm damage (XT) and above the collar damage (ACD). Results The results showed high differences in the PD, XI, XO and XT caused by weevils from the different zones. PD and XT ranged from 4.8–50.4 to 4.2–43.8%, respectively, caused by weevils collected from Kabale and Rakai, Kabale and Wakiso, respectively, while XI and XO varied from 0.0–42.9 to 8.3–40.4%, respectively, caused by banana weevils collected from Kabale and Rakai, Kabale and Rakai, respectively. Banana weevils from Rakai caused the highest ACD of 40.4% and no such damage was caused by banana weevils collected from western Uganda. Average ACD in suckers was 19.6% and significantly higher than that in tissue culture plants (8.5%). Conclusions and recommendations Corm damage assessment suggests the existence of banana weevil biotypes but it is recommended that follow-up studies be carried out to confirm this phenomenon.